Research on the Strategy of Deep Integration of “Production, Education, Research and Training” of High-level Nursing Professional Group in China - Lu, Suli; Liu, Bo (Journal of Educational Research and Policies, 2025)
With the continuous upgrade of medical and health demands, the high-level development of nursing professional groups has become increasingly urgent. This study compares the current development status of nursing professional groups both domestically and internationally, revealing the existing differences and issues in the development of these groups. Based on in-depth theoretical analysis and successful integrated cases from both domestic and international contexts, this paper constructs a theoretical framework for the integration model of production, education, research, and training. Based on this framework, strategies for the deep integration of nursing professional groups that are suitable for China’s conditions are proposed. The strategies include improving the policy environment, strengthening regulatory support, and detailing specific implementation pathways and methods. Ultimately, this research clarifies the significant importance of the deep integration model for the development of nursing professional groups and highlights its practical value and guiding significance in promoting nursing education and industry development in China.